Evaluation of Tunisian Olive Leaf Extracts to Reduce the Bioavailability of Acrylamide in Californian-Style Black Olives - Dalel Mechi; Francisco Pérez-Nevado; Ismael Montero-Fernández; Bechir Baccouri; Leila Abaza; Daniel Martín-Vertedor (MDPI AG, 2023)
The aim of this work was analyzing the use of olive leaf extracts (OLE) obtained from two local Tunisian olive tree cultivars 'Chemlali' and 'Sayali' to reduce the acrylamide in Californian-style black olives. The phenol profile, antioxidant, and antibacterial activity of the two OLE extracts were evaluated. The principal phenols found were hydroxytyrosol (1809.6 ± 25.3 mg 100 g−1), oleuropein (2662.2 ± 38 mg 100 g−1) and luteolin-7-O-glucoside (438.4 ± 38 mg 100 g−1) presented higher levels in 'Sayali' variety. Small differences were observed between the two kinds of extracts used; the greatest activity of OLE was observed against S. choleraesuis, with values up to 50% inhibition. The extract of 'Chemlali' cultivar was added to the Californian-style table olive, improving its phenol content and its antioxidant characteristics without negatively affecting its sensorial characteristics; these olives showed the highest firmness and proper quality characteristics. The gastrointestinal activity on the acrylamide concentration showed a partial degradation of this compound through the digestion, although the addition of the extract does not seem influence in its gastrointestinal digestion. These findings prove the usefulness of by-products to generate a high-quality added-value product, and this would also be relevant as a step towards a more sustainable, circular economy model.